Models of Russia's Macroeconomic Policy at the Turn of the 21st Century - Vyacheslav Stolbov (Comparative Economic Research, 2010)
At present the modelling of macroeconomic processes appears to hold theoretical as well as applied interest. Hence, in the present article this method is used with regard to the Russian economy, presenting its actual economic practice in the last decade of the 20th and at the beginning of the 21st century. The author describes three macroeconomic models, taking into consideration the fact that the country is being profoundly influenced by the global financial crisis. The discussed models are: transition economy model, economic growth model and crisis-management model.